Human papillomavirus vaccination related knowledge, and recommendations among healthcare providers in Southern China: a cross-sectional survey - Siqi Chen; Chaofan Mei; Weikang Huang; Peiyi Liu; He Wang; Wei Lin; Shixin Yuan; Yueyun Wang (BMC Women's Health, 2022)
Abstract Background Little research has been conducted to explore variables associated with the healthcare providers’ (HCPs) understanding and recommendation of human papillomavirus vaccine (HPV) since the vaccine was approved for use in China. Methods A large-scale cross-sectional survey was conducted in southern China covering Guangdong, Guangxi, and Hainan provinces between April 2019 and October 2019. Firstly, descriptive analysis was used to access awareness, knowledge, barriers, and recommendations toward HPV vaccine among all participants. Multi-variable logistic regression was further applied to explore potential factors associated with awareness, acknowledgment of HPV vaccine, and recommendation behaviors toward HPV vaccine. Results 2075 questionnaires were collected, and 2054 were included in the final analysis. In total, 77.9% of participants have heard of HPV vaccine and obtained sub-optimal HPV/HPV vaccine knowledge scores with a mean (SD) of 13.8 (3.5) out of a maximum score of 23. 68.1% HCPs reported that they have recommended HPV vaccine to others. Province and profession were the most significant characteristics associated with awareness, knowledge score, and recommendation behavior toward HPV vaccine. HCPs in Guangdong obtained a much better knowledge score [Mean (SD) = 15.5 (3.0)] and reported higher recommendation behavior (82.8%). Compare with HCPs from the Division of Expanded Program on Immunization (DEPI), Community Health Center (CHC), and obstetrician-gynecologists, other non-HPV closely related professions showed a less competent knowledge of HPV and HPV vaccine [Mean (SD) = 12.5 (3.0)] and lower frequency of recommendation behavior on vaccination (58.1%). The difference in HPV vaccine knowledge among different professions was concentrating on the items about clinical pathology of HPV and the practical aspects of HPV vaccine. Educational level and title were also closely associated with their knowledge of HPV and its vaccine. Besides, knowledge scores independently determined with recommendation behavior (OR = 1.18, 95% CI 1.13–1.23). Conclusion Knowledge level of HPV and HPV vaccine as well as recommendation behavior toward HPV vaccine were relatively lower in southern China and differed significantly between provinces. Profession-specific gaps on the knowledge level of HPV and HPV vaccine emphasized the need for targeted education and training to improve HCPs’ engagement in the promotion of the HPV vaccine.